(untitled) (Journal of Asian Development Studies, 2026)
Research with children and youth is complicated as one has to face the challenge of unequal power relations between researcher, children and youth. This ethnographic research was carried out with fourteen boys working on the streets aged 12-16. These boys belong to two different ethnic groups, the Afghan and Pathan, and reside in Rawalpindi city. In this research, different qualitative tools and techniques were used but mainly photo-elicitation was used to get an in-depth understanding of young people’s daily lives . It was found that photo-elicitation technique helped to create fun and learning among the key informants on the one hand and provided major research insights on the other. It is concluded that photo-elicitation gave opportunity to boys to express innovatively, a process which not only empowered them but also gave them a chance to think critically and raise their voices.